Systematic review of published phase 3 data on anti-PCSK9 monoclonal antibodies in patients with hypercholesterolaemia - Gouni-Berthold, Ioanna; März, Winfried (British journal of clinical pharmacology, 2016)
Aims Two anti-proprotein convertase subtilisin/kexin type 9 (PCSK9) monoclonal antibodies, alirocumab and evolocumab, have been approved for the treatment of hypercholesterolaemia in certain patients. We reviewed data from Phase 3 studies to evaluate the efficacy and safety of these antibodies. Methods We systematically reviewed Phase 3 English-language studies in patients with hypercholesterolaemia, published between 1 January 2005 and 20 October 2015. Congress proceedings from 16 November 2012 to 16 November 2015 were also reviewed. Results We identified 12 studies of alirocumab and nine of evolocumab, including over 10 000 patients overall. Most studies enrolled patients with hypercholesterolaemia and used anti-PCSK9 antibodies with statins. The ODYSSEY FH I, FH II and HIGH FH alirocumab studies and the RUTHERFORD-2 evolocumab study exclusively recruited patients with heterozygous familial hypercholesterolaemia. Two evolocumab studies focused mainly on homozygous familial hypercholesterolaemia (HoFH): TESLA Part B and TAUSSIG (a TESLA sub-study); only those data for HoFH are reported here. All comparator studies demonstrated a reduction in LDL cholesterol (LDL-C) with the anti-PCSK9 antibodies. No head-to-head studies were conducted between alirocumab and evolocumab. Up to 87% of patients receiving alirocumab and up to 98% receiving evolocumab reached LDL-C goals. Both antibodies were effective and well tolerated across a broad population of patients and in specific subgroups, such as those with type 2 diabetes. Conclusions Using anti-PCSK9 antibodies as add-on therapy to other lipid-lowering treatments or as monotherapy for patients unable to tolerate statins may help patients with high cardiovascular risk to achieve their LDL-C goals.